PENGARUH BEBAN PROMOSI, BIAYA PRODUKSI DAN PERTUMBUHAN PENJUALAN TERHADAP LABA PERUSAHAAN - Ade Elina; Susi Handayani (Equilibrium: Jurnal Penelitian Pendidikan dan Ekonomi, 2021)
This study aims to provide empirical evidence regarding the effect of promotional costs, production costs and sales growth on company profits in manufacture companies on the Indonesia Stock Exchange for the period 2017-2019. Profit is the result of the difference between the income from the resource or income with the expenditure of the resource or expense for its existence. Companies need to reduce any costs incurred to get a profit, one of which is promotional expenses. Promotional expenses, namely promotional budget expenditures to acquire customers for products that have been issued by the company. In addition to promotional expenses, companies need to reduce production costs. Production costs are the sacrifice of a number of costs during the production process, starting from raw materials to products that are ready to be purchased by consumers. Company profits can be obtained from sales activities. Sales growth is an increase or decrease in sales from year to year from a company. The research sample consisted of 84 manufacture companies. The data analysis technique used in this study is multiple linear regression. Hypothesis test results show that both partially and simultaneously promotional expenses, production costs and sales growth have a significant effect on company profit. Keywords :, production costs; profits; promotional expenses; sales growth